Exercise, Training & Health - Vantorre A; Schellhammer F (Deutsche Zeitschrift für Sportmedizin, 2022)
Injuries of the hamstrings are well known in all kinds of sports. According to the associated mechanisms, literature divides between a running and a stretch type lesion. A variant of the stretch type has been observed in sports climbing based on two almost identical lesions of the hamstrings due to high-elevation heel hooking. This specific movement is characterised by isometric muscle tension in extensive hip flexion with a flexed knee. Even without an obvious trauma, we found severe injuries of the proximal hamstrings. These may cause serious consequences to the further career of a climber. Trainers and route setters should keep this in mind.Key Words: Musculoskeletal, MRI, Route Setting